Designing a Multimodal Workbook for Prospective EFL Teachers in the Academic Writing Context - Yana, Dewi; Rozimela, Yenni; Hamzah, Hamzah (Journal of Languages and Language Teaching, 2025)
Proficiency in multimodal writing is becoming progressively crucial for students, particularly in the realm of academic writing. Nevertheless, the existing learning materials in higher education fail to adequately meet those requirements. Hence, the goal of this study is to create a workbook that will assist students in improving their ability to write using various modes in academic writing classes. This study employs Research and Development, with a specific focus on the Analysis and Design phases of the ADDIE approach. The investigation had a total of 114 participants. We employed triangulation techniques to develop a questionnaire and gathered data in July 2024. Subsequently, we analyzed and displayed the data using descriptive statistics, elucidating its meaning in accordance with the pre-established categories. The requirements assessment revealed that students necessitate support in academic writing, including obtaining credible sources, employing technological tools, completing plagiarism checks, and maintaining citations. Students desire a customizable learning structure that allows them to produce multimodal (digital) texts and engage in activities both individually and collaboratively. The needs analysis determines the structure of the multimodal project workbook, which consists of five sections arranged according to the syntax of project-based learning. To achieve more effective and practical outcomes, it is critical to proceed with the research by carrying out the Development and Implementation stages.